Smart Control of Traffic Light Using Artificial Intelligence - M. Sravani,; S. Geetha Sri Priyanka,; K.N.V.K Sairam,; K. Krishna Murthy, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Traffic light management is one of the intense technical hazards of the urban areas in almost every country around the world. This is due to speedy increase in number of vehicles in order to decrease the time and complexity. The project developed by us will enable the traffic light to switch from red to green based on traffic density. The easy way to control a traffic light by using timer for each section since, we proposed a system for controlling the traffic light by image processing. The system can notice vehicles through pictures and also the image sequence can then be analyzed victimization digital image process for vehicle detection, and in line with traffic conditions on the road stoplight will be controlled.
Keywords: Computer Vision; Traffic management; Traffic light system; Traffic congestion; Artificial intelligence; Smart surveillance